Dermatologic clinical case - Santos, Raquel; Quintela, Carolina; Azevedo Silva, Joana; Peralta, Lígia; Sá, Aida (BIRTH AND GROWTH MEDICAL JOURNAL, 2025)
Phytophotodermatosis (PPD) is a skin reaction caused by contact with furocoumarins, photosensitizing substances present in certain plants, followed by exposure to ultraviolet radiation. Herein we report a case of a 17-year-old teenager who developed a cutaneous reaction after using rue (Ruta graveolens) as a homemade treatment for acne. The condition presented with a characteristic inflammatory phase, followed by a hyperpigmentation phase. A diagnosis of PPD due to rue was established, and with rue eviction there was a full resolution. The authors aim to raise awareness about this condition which requires a high level of clinical suspicion for identifying the etiological agent. Prompt recognition and intervention are crucial in preventing the worsening and recurrence of the reaction.